201k views
2 votes
Y=2x-1 4x +3y=7 solve ​

Y=2x-1 4x +3y=7 solve ​-example-1
User Msonic
by
5.5k points

1 Answer

4 votes

Answer:

(1, 1)

Explanation:

given the 2 equations

y = 2x - 1 → (1)

4x + 3y = 7 → (2)

Substitute y = 2x - 1 into (2)

4x + 3(2x - 1) = 7 ← distribute and simplify left side

4x + 6x - 3 = 7

10x - 3 = 7 ( add 3 to both sides )

10x = 10 ( divide both sides by 10 )

x = 1

Substitute x = 1 into ( 1) and evaluate for y

y = (2 × 1) - 1 = 2 - 1 = 1

Solution is (1, 1 )

User Wuffwuff
by
5.1k points